2015
DOI: 10.1371/journal.pone.0138353
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Gene Flow from Sexual to Asexual Lineages in Thrips tabaci (Thysanoptera: Thripidae)

Abstract: Populations of Thrips tabaci are known to have two sympatric but genetically isolated reproductive modes, arrhenotoky (sexual reproduction) and thelytoky (asexual reproduction). Herein, we report behavioral, ecological and genetic studies to determine whether there is gene flow between arrhenotokous and thelytokous T. tabaci. We did not detect significant preference by arrhenotokous males to mate with females of a particular reproductive mode, nor did we detect significant behavioral differences between arrhen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 51 publications
3
28
3
Order By: Relevance
“…tabaci as a cryptic species complex even though ongoing gene flow occurs. Results from this study and Li et al 2015 [ 15 ] show that gene-flow events are rare; however, it is not clear whether or not offspring produced from these events persist in the environment. Future studies examining both gene flow among different clonal groups of T .…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…tabaci as a cryptic species complex even though ongoing gene flow occurs. Results from this study and Li et al 2015 [ 15 ] show that gene-flow events are rare; however, it is not clear whether or not offspring produced from these events persist in the environment. Future studies examining both gene flow among different clonal groups of T .…”
Section: Discussioncontrasting
confidence: 65%
“…Phylogenetic relationships examined using ML methods in MEGA identified two major clades in this study, which corresponded to lineages 2 and 3 ( Fig 2 ) [ 1 , 6 , 7 , 9 , 17 ]. Most haplotypes collected in this study were previously reported in New York: lineage 3 haplotypes NY-HT1, NY-HT2/NY-HT5 (these two could not be distinguished based on the sequences used in this analysis), NY-HT3, NY-HT6 [ 17 ], and lineage 2 haplotype, here designated as NY-HA1 [ 15 ]. Two new haplotypes in lineage 2, NY-HA2 (Genbank: KR152257), and NY-HA3 (Genbank: KR152258) were identified in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth pointing out that in its current form, our method is not able to detect incidental gene flow between thelytokous and arrhenotokous individuals. Li et al (2015) published evidence about interbreeding by detecting gene flow between the progeny of leek-associated arrhenotokous (L1) males and leek-associated thelytokous (L2) females. Due to the successful mating between different lineages, the male-originated nuclear gene allele (histone H3 gene) was present in the progenies, although in only very low proportions.…”
Section: Discussionmentioning
confidence: 99%
“…The parasite's life cycle thus likely represents a continuum of bottlenecks linked to frequent local extinction and recolonization events that increase levels of genetic drift and identity by descent (IBD). It may thus come to less surprise that observations of diffuse hybrid clonality around a restricted focus of sex in BM resemble spatio-temporal patterns of heterogony demonstrated in various other metapopulation systems (50)(51)(52)(53)(54)(55)(56)(57)(58). Facultative sex often coincides with strong metapopulation structure, in which sexual variants are predicted to occupy core habitat (where population subdivision and inbreeding depression is minimized) while asexual variants disperse more freely without fitness costs from close IBD during frequent founding events (59).…”
Section: Rationale For Reproductive Polymorphism In T Cruzimentioning
confidence: 99%